PENERAPAN RENCANA STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN DENGAN MENGGUNAKAN METODE ANALISIS SWOT, DAN BCG MATRIX (STUDI KASUS PADA UKM TOM BATIK) - Mhd Andry Kurniawan; Sispa Pebrian; Nur Hasnah AR; Imelda Yunita; Rahmadini Payla Juarsa; Niskan Walid Masruri; Pramana Angga (Fakultas Pertanian, Universitas Riau, 2022)
AbstractTom Batik is one of “Usaha Kecil Menengah (UKM)” in Kulon Progo Region which is running on batik cloth priduction. These UKM always want to develop by providing the best quality of batik. This study uses SWOT analyze which aims to determine the various factors systematically to formulate a strategy. This analysis is based on the logic that can maximize the strenght and opportunities, but at the same time can minimize the weaknesses and threat. Moreover, the author also uses the BCG Matrix which aims to develop a balance between the various product portfolios and determine the position of the UKM’s market. In this study, distributed the questionnaire which contains 5 attributes of consumer needs. The results of the questionnaire showed that the expected level of consumer satisfaction is different with the state of UKM still today. SWOT analyze and BCG matrix which function is to provide strategies to UKM are used to overcome these problems. Based on the calculation, the calculation of Internal matrix and Eksternal matrix showed that Tom Batik was on the first quadrant ( aggressive ) with a 0.03 towards to the strenght and 2.00 towards the the opportunities , which means that Tom Batik has a very favorable situation . While the market position of Tom Batik which is obtained from BCG Matrix is located on the Question Mark position of market growth in 2011-2012 as many as 20 % and Relative Market Share as many as 0.4 . Business strategies which are suggested to companies for promotion optimizing among others in the community , give a view to the public that batik is a traditional Indonesian clothing , further enhance product innovation , always maintaining the environment preservation so that the raw material of natural dyes will not extinct . It aims to increase the sales volume and revenues of UKM, so that UKM can get out of the competition .Keywords: SWOT, BCG, Tom Batik, Strategy